Barriers and facilitators to participation in breast, bowel and cervical cancer screening in rural Victoria: A qualitative study. (27th March 2021) - Azar, Denise; Murphy, Michael; Fishman, Alana; Sewell, Lauren; Barnes, Megan; Proposch, Amanda
Abstract: Issue addressed: Population cancer screening rates are around 50% for the general population and even lower in rural areas. This study aimed to explore knowledge, attitudes, behaviours, motivators and barriers to breast, bowel and cervical screening participation in under‐screened men and women. Methods: We used a qualitative research design. Focus groups were segmented by age, sex and screening participation. Participants were under‐screened in at least one of the cancer screening programs, with separate groups for each of the programs. The discussion guides were designed around the Health Belief Model and group discussions were coded using a thematic content analysis approach. Results: Fourteen focus groups were held with 80 participants. Key themes were that the concept of cancer screening was not well understood, a low priority for preventive health behaviours, issues relating to local general practitioners (GP) and screening was unpleasant, embarrassing and/or inconvenient. A key determinant of participation in cancer screening was exposure to prompts to action, and it was evident that participants often required multiple prompts before they took action. Conclusions: Opportunities that develop attitudes to health that place disease prevention as a high priority; improve understanding of the benefit of screening in terms of early detection and treatment; improve GP availability and the patient‐practitioner relationship; and the development of messages for each of the screening programs should be further explored as factors that may influence rural population screening rates. So what?: Addressing health attitudes, beliefs, knowledge, health practitioner and test‐related barriers and improving messaging may increase cancer screening participation in under‐screened rural populations.